2020
DOI: 10.1097/md.0000000000021266
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center study for acupuncture combined with Chinese medicine in the treatment of chronic spontaneous urticaria based on the theory of taking shu-stream points when the disease is aggravated

Abstract: Chronic spontaneous urticaria (CSU) is a common dermatologic disease that seriously affects patient quality of life. The choice of therapy to control the disease and prevent its recurrence has always presented a difficult clinical issue. Previous studies have shown that traditional Chinese medicine is a safe and effective treatment for CSU. Recently, the temporal rhythms of CSU, a disease characterized by intermittent flares of active disease and periods of little or no disease, have attracted the attention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The TCM has unique advantages in AD routine management and treatment. The efficacy of its classic herbal formulation AYZ is scientifically and clinically proven and has been widely used in the treatment of chronic urticaria, hypersensitivity, pruritus and AD without any severe adverse events ( Qin et al, 2020 ). The AYZ formula comprises of 11 different herbs including, Angelica sinensis (Oliv.)…”
Section: Introductionmentioning
confidence: 99%
“…The TCM has unique advantages in AD routine management and treatment. The efficacy of its classic herbal formulation AYZ is scientifically and clinically proven and has been widely used in the treatment of chronic urticaria, hypersensitivity, pruritus and AD without any severe adverse events ( Qin et al, 2020 ). The AYZ formula comprises of 11 different herbs including, Angelica sinensis (Oliv.)…”
Section: Introductionmentioning
confidence: 99%
“…e results after 4 weeks of treatment were used as the criterion for the clinical efficacy evaluation [12]. Clinically cured: after treatment, the patient's symptom score was decreased by 95% or more as compared with that before treatment, and his wheal, flushing, and itching completely disappeared.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…[7] Increasing studies have shown that Chinese medicine combined with acupuncture has a significant effect on chronic urticaria, which can treat both symptoms and root causes. [8] Currently, there is a lack of systematic evidence-based medical evidence on the efficacy and safety of Chinese medicine combined with acupuncture in the treatment of chronic urticaria. Therefore, this article aims to conduct a meta-analysis of the literature on the treatment of chronic urticaria with TCM combined with acupuncture, and compare the efficacy and safety differences between acupuncture combined with conventional Western medicine, so as to provide guidance for the clinical treatment of chronic urticaria.…”
Section: Introductionmentioning
confidence: 99%